The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11934-020-00984-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Encourage Medical Student Interest in Urology

Abstract: Purpose of Review Urology residency positions have steadily increased but applications have remained stagnant. This is an alarming trend given the aging general population and thus increased need for urologists. The purpose of this review is to describe barriers and suggest strategies to encourage medical students to pursue urology. Recent Findings Barriers to interest in urology include educational factors, such as timing of exposure to urology in medical school, USMLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…Conversely, medical student exposure to urology in Australia is greater, with 82% of surveyed students exposed to urology during clinical placement. Studies outside Australia have shown duration of urology placement is predictive of selection of urology as a specialty 4,5 but we did not find this to be the case. However, significantly more students in our study wanted more exposure to urology.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Conversely, medical student exposure to urology in Australia is greater, with 82% of surveyed students exposed to urology during clinical placement. Studies outside Australia have shown duration of urology placement is predictive of selection of urology as a specialty 4,5 but we did not find this to be the case. However, significantly more students in our study wanted more exposure to urology.…”
Section: Discussioncontrasting
confidence: 81%
“…Studies outside Australia show exposure to urology is the most significant predictor for medical students selecting urology as a specialty but other factors such as gender, presence of a mentor and perceptions of urology training and practice may play a part. 4,5 Few medical students in Australia have formalized urology rotations 6 and there have been no Australian studies on factors that influence their decision to consider urology.…”
Section: Introductionmentioning
confidence: 99%
“…Early exposure to urology requires preclinical exposure to urology, such as urology faculty involved in teaching first- and second-year students and supporting urology interest groups. 6 It has been shown that mentors and medical teachers were among the most important influences in a URiM student’s decision to pursue urology, 7 but URiMs only make up 3.9% of medical school faculty 8 and are less likely to be in a subspecialty or participate in research.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge would enable the urology IG to fulfill its purpose for all students-to create interest, support that interest, and remove barriers for students considering urology. 22 Possible avenues of recruitment could involve collaboration between IGs and student groups like Student National Medical Association, Latino Medical Student Association, and Association of Native American Medical Students.…”
Section: Discussionmentioning
confidence: 99%